Lamin A precursor localizes to the Z-disc of sarcomeres in the heart and is dynamically regulated in muscle cell differentiation. (21st November 2022) - Brayson, Daniel; Shanahan, Catherine M.
Abstract : The lamin A precursor, prelamin A, requires extensive processing to yield mature lamin A and effect its primary function as a structural filament of the nucleoskeleton. When processing is perturbed, nuclear accumulation of prelamin A is toxic and causes laminopathic diseases such as Hutchinson–Gilford progeria syndrome and cardiomyopathy. However, the physiological role of prelamin A is largely unknown and we sought to identify novel insights about this. Using rodent heart tissue, primary cells and the C2C12 model of myofibrillogenesis, we investigated the expression and localization patterns of prelamin A in heart and skeletal muscle cells. We found that endogenous prelamin A was detectable in mouse heart localized to the sarcomere in both adult mouse heart and isolated neonatal rat cardiomyocytes. We investigated the regulation of prelamin A in C2C12 myofibrillogenesis and found it was dynamically regulated and organized into striations upon myofibril formation, colocalizing with the Z-disc protein α-actinin. These data provide evidence that prelamin A is a component of the sarcomere, underpinning a physiological purpose for unprocessed prelamin A. This article is part of the theme issue 'The cardiomyocyte: new revelations on the interplay between architecture and function in growth, health, and disease'.